2009
DOI: 10.3941/jrcr.v3i3.42
|View full text |Cite
|
Sign up to set email alerts
|

Geniculate arterial pseudoaneurysm formation following trauma and elective orthopaedic surgery to the knee: 2 case reports and a review of the literature

Abstract: Arterial pseudoaneurysm formation of the genicular vessels following orthopaedic surgery to the knee is an extremely rare occurrence. Here we report the successful management of two cases as a complication of total knee arthroplasty and a tibial interlocking nail, utilising coil embolisation by interventional radiological techniques and negating the need for further surgery. To our knowledge this is one of the few reported cases of pseudoaneurysms of the descending genicular artery secondary to drain placement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…Most arise as complications from total knee arthroplasty, 7,8 while the few other cases have been documented following blunt force trauma 10,11 and internal fixation. 12 The most concerning feature of pseudoaneurysms is their often silent presentation. Rich et al 2 found that the diagnosis can be delayed from 1 to 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Most arise as complications from total knee arthroplasty, 7,8 while the few other cases have been documented following blunt force trauma 10,11 and internal fixation. 12 The most concerning feature of pseudoaneurysms is their often silent presentation. Rich et al 2 found that the diagnosis can be delayed from 1 to 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair with vessel ligation, US-guided thrombin injection, and embolization have all been described as management for geniculate artery pseudoaneurysms, though surgery was performed in 75% of cases with primary embolization in 21% [1,2]. Embolic agents previously used with reported success include coils and gelfoam [3,4]. However, there remains a paucity of data on the relative efficacy of each agent and no prior direct comparisons with other forms of intervention.…”
Section: Glue Embolization Of a Traumatic Geniculate Artery Pseudoanementioning
confidence: 99%
“…Metode ini mempunyai tindakan invasif minimal dengan angka kesuksesan yang tinggi, komplikasi lebih sedikit serta angka kematian yang lebih kurang dibandingkan pembedahan. 20 Terapi intervensi yang terbaru termasuk kompresi dengan tuntunan USG, manajemen perkutaneus secara langsung (misalnya injeksi trombin dengan tuntunan USG) dan manajemen endovaskular (embolisasi dan implan stent-graft). Kompresi dengan tuntunan USG sangat bermanfaaat untuk pseudoaneurisma superfisial paska kateterisasi, seperti arteri femoralis dan brakhialis.…”
Section: Bahasanunclassified